Дар: [роман] / Джулия Гарвуд ; [пер. с англ. Т. Замиловой] - Гарвуд Джулия (Алая роза, 1994)
Экземпляры: с/ф № 8 (20140324) / Инвентарный номер: 43236 / Цена: / Сис.шифр: 84И / Авт.знак: Г 20 / ГРНТИ: 17.82.31 / ББК: 84(7)